Hexachlorobenzene (HCB) adsorption onto the surfaces of C60, C59Si, and C59Ge: Insight from DFT, QTAIM, and NCI - Mohsen D. Mohammadi; Hewa Y. Abdullah; Hitler Louis; Emmanuel E. Etim; Henry O. Edet; Obinna C. Godfrey (Chemical Physics Impact, 2023)
Several reports have shown that nanomaterials have been found to be effective for gas sensing application and the adsorption of hazardous organochloride. Herein, dispersion corrected density functionals; D3-B3LYP-D3, ωB97XD, M06-2X and PBE0 all at the 6-311G (d) basis set was used to study the interactions of metal-doped fullerenes (silicon (C59Si) and germanium (C59Ge)) with Hexachlorobenzene (C6Cl6) gas molecule. The adsorption properties of the adsorbents viz; the pure fullerene nanocage (C60) and the doped system; Silicon (C59Si) and Germanium (C59Ge) were all investigated in terms of reactivity, stability, bond order, intermolecular interaction, van der waals, and weak interaction as well as adsorption energy. The reactivity levels of the examined surfaces were observed within the same range at the B3LYP-D3/6-311G (d) level of theory to be 5.996 eV, 5.309 eV, and 5.188 eV for C60, C59Si and C59Ge adsorbents respectively. From our calculation for adsorption energies; the high negative value -1.010 eV of for the C59Ge nanocage suggests that the doped surface adsorbs hexachlorobenzene better in comparison to the other surfaces and adsorption is thermodynamically favored. The results for natural bond orbitals (NBO), quantum theory of atoms in molecules (QTAIM), and non-covalent interaction (NCI) were consistent across all systems and favored physical adsorption.